The anticancer activity and mechanisms of She medicine herbs - Miao, Yunxuan; Chen, Yisheng; Lan, Qiaofen; Chen, Ruogu; Zhuang, Jiajia; Shi, Haojun; Wang, Miao; Miao, Jianhui; Lin, Chengshou (Frontiers in Pharmacology, 2025)
She Medicine, a traditional therapeutic system from China’s She ethnic group, shows promise in cancer treatment. This paper provides a comprehensive review of She medicinal herbs, focusing on their anticancer activities and underlying mechanisms. Compared to widely studied traditional medicines (e.g., Traditional Chinese Medicine), She Medicine exhibits unique ethnopharmacological traits, such as localized plant usage and multi-target mechanisms involving apoptosis induction, immune modulation, and tumor microenvironment regulation. Key herbs like Pimpinella diversifolia and Melastoma dodecandrum showing significant anticancer potential due to their bioactive compounds such as flavonoids, quercetin, and gallic acid. For example, homoharringtonine (HT), a She-derived alkaloid, targets Smad3/TGF-β pathways in non-small cell lung cancer and synergizes with chemotherapy in leukemia treatment, as evidenced by preliminary clinical trials. However, challenges persist, including resource shortages, insufficient mechanistic studies, and a lack of quality control standards. Future research should integrate multi-omics and bioengineering approaches to standardize She Medicine and bridge its traditional use with modern therapies such as immune checkpoint inhibitors. Overall, She medicinal herbs hold great promise for cancer treatment and warrant further exploration to unlock their full potential in modern medicine.